2013
DOI: 10.1371/journal.pone.0077500
|View full text |Cite|
|
Sign up to set email alerts
|

Choosing between an Apple and a Chocolate Bar: the Impact of Health and Taste Labels

Abstract: Increasing the consumption of fruit and vegetables is a central component of improving population health. Reasons people give for choosing one food over another suggest health is of lower importance than taste. This study assesses the impact of using a simple descriptive label to highlight the taste as opposed to the health value of fruit on the likelihood of its selection. Participants (N=439) were randomly allocated to one of five groups that varied in the label added to an apple: apple; healthy apple; succu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
1
8
0
2
Order By: Relevance
“…Importantly, these effects were observed while controlling for a number of psychological constructs, including measures of food beliefs and goals that also predicted fruit choice. This suggests that age and education appear to have an impact on food preferences not explained by the psychological variables that predicted fruit selection in the current study, including explicit food goals and the belief that unhealthy foods generally taste better ( Raghunathan et al., 2006 ), in line with previous studies ( Forwood, Walker, Hollands, & Marteau, 2013; Glanz et al., 1998 ).…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, these effects were observed while controlling for a number of psychological constructs, including measures of food beliefs and goals that also predicted fruit choice. This suggests that age and education appear to have an impact on food preferences not explained by the psychological variables that predicted fruit selection in the current study, including explicit food goals and the belief that unhealthy foods generally taste better ( Raghunathan et al., 2006 ), in line with previous studies ( Forwood, Walker, Hollands, & Marteau, 2013; Glanz et al., 1998 ).…”
Section: Discussionsupporting
confidence: 83%
“…Although there is increasing interest in how different factors are associated with food, how these “top down” signals differentially influence food choice remained elusive. For example, in a recent behavioral study on the use of simple descriptive food labels to promote healthy food choices, it was found that interventions that emphasize the taste of healthier foods are likely to be more effective at achieving healthier diets than those emphasizing health alone [ 13 ]. Furthermore, it has been suggested that extra attention should be paid to the tastefulness of healthy food products.…”
Section: Discussionmentioning
confidence: 99%
“…Taste was shown the most chosen as the first criterion in food choice [ 12 ]. A direct comparison between taste and health associations showed that the taste of an apple was indeed a stronger predictor of individual dessert choice as compared to its assigned health score [ 13 ]. Furthermore, food choices were guided by information about time of the consumption (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Outro estudo mostrou que participantes expostos a rótulos, que ressaltavam tanto o sabor como os aspectos saudáveis de uma maçã, a selecionaram significativamente mais comparados aos participantes que viram a maçã sem qualquer descritor. 75 Portanto, algumas evidências no âmbito da Neurobiologia apontam para a modulação das respostas autonômicas e dos circuitos cerebrais por frases textuais.…”
Section: -62unclassified